1996
DOI: 10.1042/bj3190027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a cDNA coding for GTP cyclohydrolase I from Dictyostelium discoideum

Abstract: The GTP cyclohydrolase I (GTP-CH) gene of the cellular slime mould Dictyostelium discoideum has been cloned and sequenced. The 855 bp cDNA of this gene contains the open reading frame (ORF) encoding 232 amino acids with a predicted molecular mass of approx. 26 kDa. Southern blot analysis indicated the presence of a single gene for GTP-CH in Dictyostelium. PCR amplification of the ORF from chromosomal DNA and sequencing showed the existence of a 101 bp intron in the GTP-CH gene of Dictyostelium discoideum. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…However, the genomic structure of GTP cyclohydrolase I varies considerably between these species : whereas the Saccharomyces cere isiae gene consists of only one exon [22] and the Dictyostelium discoideum gene of two exons interrupted by a 101 bp intron [19], the exon-intron structure of Physarum resembles those found for Drosophila [5] and mammals [20]. As can be seen from Figure 2, Physarum GTP cyclohydrolase I is structured into seven exons.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…However, the genomic structure of GTP cyclohydrolase I varies considerably between these species : whereas the Saccharomyces cere isiae gene consists of only one exon [22] and the Dictyostelium discoideum gene of two exons interrupted by a 101 bp intron [19], the exon-intron structure of Physarum resembles those found for Drosophila [5] and mammals [20]. As can be seen from Figure 2, Physarum GTP cyclohydrolase I is structured into seven exons.…”
Section: Resultsmentioning
confidence: 86%
“…Physarum intron 4 is at a homologous position to the only Dictyostelium intron (Figure 2). Physarum introns 2 and 5 have no corresponding introns in the other species studied so far (for a summary of the exon-intron structures of various species see [19]). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of E. coli, the required four steps of this transformation are carried out by the folE gene product (6). Genes encoding highly conserved sequences homologous to the sequence of this enzyme have been identified from a wide range of different Eucarya and Bacteria (12), and in a few cases, the proteins have been cloned, sequenced, overexpressed, and shown to catalyze the expected reaction (8,25). Early labeling experiments using archaea indicated that GTP cyclohydrolase I also catalyzed the first committed step in the biosynthesis of the pterin portion of the modified folate, methanopterin (9,20).…”
mentioning
confidence: 99%